Enhancing the Quality of Life for Thai Elderly through Tourism: Insights from the Private Sector - Tuntideelert, Masarus; Kono, Shayaniss (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
As Thailand transitions into a complete aged society, improving the quality of life for seniors has become a key socio-economic priority. Tourism stands out as a powerful tool for promoting comprehensive well-being in this demographic. This research article aims to analyze the tourism models developed by the private sector to enhance the quality of life for the elderly, and to propose guidelines for sustainable senior tourism development from a private-sector perspective. This qualitative study gathered data from documents, publications, and websites, as well as interviews with eight entrepreneurs, tour guides, and tour leaders who operate businesses related to or specifically serve elderly travelers. The data was subsequently subjected to content analysis through the researchers’ perspective. The research findings indicate that private sector entrepreneurs play a vital role in designing activities and services that promote the physical, mental, and social well-being of the elderly, with a primary focus on safety and age-appropriate experiences. However, the costs associated with both private and group tours vary significantly. This cost factor may act as a major barrier to tourism access for the Thai elderly. Consequently, a multi-stakeholder collaboration involving government agencies, the private sector, independent organizations, and local communities is essential to ensure long-term continuity and sustainability. In conclusion, the CHAN Model—comprising Cultural, Health, Soft Adventure, and Nature tourism—is proposed as an integrative framework to strengthen and standardize the Thai senior tourism sector. Briefly, cultural tourism helps boost cognitive and mental stimulation, social integration and reduced isolation, and sense of purpose and self-worth. Health tourism raises physical rejuvenation and pain management, mental health and stress reduction, and empowerment and autonomy. While soft adventure tourism lifts physical vitality and functional mobility, nature tourism uplifts psychological restoration and sensory stimulation. If these four tourism sectors are well-integrated, they create a “quadruple-win” scenario.